Artificial Intelligence in Stock Market Trading - Viresh Sharma (International Journal of Advanced Science and Technology, 2019)
The stock market is an excellent sector for using AI and ML technology to make a complete analysis and accurate prediction of stock price volatility.Artificial intelligence technology has been used in the stock market for two main purposes: to increase speed and integrate data for use in rational predictive models. Investors are starting to discuss artificial intelligence technologies that will automatically increase the number of stocks that can be bought simultaneously when a given set of market parameters are met. This smart technology allows the computer system to complete 5 transactions at a time. Traders simply press a button on their computer.